2009
DOI: 10.4049/jimmunol.0900244
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Binding of Carbohydrates by the Human α-Defensin, HD5

Abstract: Four of the six human α-defensins (human neutrophil peptides 1–3 and human α-defensin 5; HD5) have a lectin-like ability to bind glycosylated proteins. Using HD5 as a model, we applied surface plasmon resonance techniques to gain insights into this property. HD5 bound natural glycoproteins > neoglycoproteins based on BSA > nonglycosylated BSA ≫ free sugars. The affinity of HD5 for simple sugars covalently bound to BSA was orders of magnitude greater than its affinity for the same sugars in soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 82 publications
5
95
0
1
Order By: Relevance
“…Further, defensins can dimerize and potentially form higher order soluble aggregates in solution (6,55). It has been demonstrated that binding of HNP1 or HD5 to gp120 or bacterial toxins promotes defensin self-aggregation (56,82). Defensin oligomerization affords additional molecular complexity at the quaternary structural level, thereby contributing to enhanced structural diversity and functional versatility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, defensins can dimerize and potentially form higher order soluble aggregates in solution (6,55). It has been demonstrated that binding of HNP1 or HD5 to gp120 or bacterial toxins promotes defensin self-aggregation (56,82). Defensin oligomerization affords additional molecular complexity at the quaternary structural level, thereby contributing to enhanced structural diversity and functional versatility.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that these surface electrostatic and hydrophobic forces, in combination with a disulfide-stabilized molecular scaffold, enable multiple defensin molecules to bind a single target protein molecule. In fact, both HNP1 and HD5 have been shown to bind bacterial toxins and HIV gp120 at a high molar ratio (56,82). Further, defensins can dimerize and potentially form higher order soluble aggregates in solution (6,55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trp-26 Mediates HNP1 Self-association-We have previously shown that ␣-defensins HNP1 and HD5 self-associate at high nM to low M concentrations, particularly in the presence of target proteins (34,62). To further examine the structural and functional role of Trp-26, we compared binding kinetics of HNP1, W26A-HNP1, and W26X-HNP1 on immobilized HNP1.…”
Section: Trp-26 Imparts Functional Versatility To Human ␣-Defensin Hnp1mentioning
confidence: 99%
“…These small, 2-5-kDa peptides are classified into ␣, ␤, and families based on sequence homology and the connectivity of disulfide bonds linking the six conserved cysteine residues (6,7). Defensins bind carbohydrates (8,9), lipids (10,11), and DNA (12) and are active against a wide range of microorganisms, including bacteria (13,14) and viruses (15)(16)(17). Defensins are also capable of interacting with an diverse array of cellular receptors and host proteins, playing important immunomodulatory functions (5,18).…”
mentioning
confidence: 99%